Knowledge, Indications and Willingness to Take Pre-Exposure Prophylaxis among Transwomen in San Francisco, 2013 - Wilson, Erin C. (PLoS One, 2015)
Safe and effective HIV prevention strategies are needed for transwomen. Transwomen in the US have a 34 times greater odds of being infected with HIV than all adults age 15-49, and in San Francisco, California 42.4% of transwomen are estimated to be infected with HIV. Pre-exposure prophylaxis (PrEP) is the first biomedical intervention with promise for reducing HIV acquisition in transwomen. However, little is known about whether transwomen know about PrEP, are taking PrEP and would be good candidates for PrEP based on their risk profile and behaviors. A population-based dataset was analyzed to determine how many transwomen in San Francisco knew about PrEP by the end of 2013 – more than a year after iPrex results demonstrated efficacy of PrEP in preventing HIV. We found that of 233 transwomen, only 13.7% had heard of PrEP. Transwomen who were living with HIV compared to those who were HIV-negative, and those who recently injected drugs compared to non-injection drug users were more likely to have heard of PrEP. Based on CDC guidelines for PrEP among MSM and IDU, 45 (30.2%) transwomen of the 149 HIV-negative transwomen in the sample were candidates for PrEP. This estimate based on CDC criteria is arguably low. Given that almost half of transwomen in San Francisco are living with HIV, this findings points to a need for further consideration of PrEP criteria that are specific and tailored to the risks for HIV faced by transwomen that are different from MSM and injection drug users. Research to scale up access and test the effectiveness of PrEP for transwomen is also urgently needed.